The Relationship of Students’ Personality, Attitude, and Spiritual Intelligence With Sportsmanship Orientation in Sports Extracurricular Activities SMP Negeri Rayon 5 Kota Semarang (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
The purpose of this study was to determine the relationship between personality, attitudes, and spiritual intelligence of students with sportsmanship orientation in sports extracurricular activities at SMP Negeri Rayon 5 Semarang. This research is a correlational study using path analysis. Pearson correlation test results; (1) personality with sportsmanship orientation shows a correlation value 0.366 with F count in table 10.833 (2) Spiritual intelligence with sportsmanship orientation shows a correlation value 0.463 with F count in table 11.023 (3) Attitudes with sportsmanship orientation show a correlation value 0.357 with an F count 6.983 (4) Personality and spiritual intelligence with sportsmanship orientation showed a correlation value 0.366 and 0.344 with an F count 7.824. (5) Spiritual intelligence and attitude with sportsmanship orientation show a correlation value of 0.344 and 0.357 with an F count of 6.921. (6) Personality and attitude with sportsmanship orientation showed a correlation value 0.366 and 0.357 with an F count 6.811. (7) Personality, attitude, and spiritual intelligence with sportsmanship showed a correlation value 0.366 and 0.357 and 0.344 with an F count 5.693. The correlation value of all variables is positive and the correlation value of all the variables is greater than r-table that is 0.158 and all F arithmetic> F table is> 3.93. The conclusion is that there is a significant relationship between personality, attitude, spiritual intelligence, and sportsmanship orientation.